1995
DOI: 10.1021/bi00027a009
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Carbonyl Group in Thioester Chain Length Recognition by the Medium Chain Acyl-CoA Dehydrogenase

Abstract: Medium chain acyl-CoA dehydrogenase from pig kidney catalyzes the oxidation of acyl-CoA thioesters to trans-2-enoyl-CoA derivatives with an optimal chain length of about C-8. The binding energy for alkyl-SCoA thioethers shows no such optimum but increases linearly from C-2 to C-16 with a slope of about 390 cal/-CH2 group. In contrast, four types of CoA-thioester analogues (2-aza-acyl-, 3-thia-acyl-, 3-keto-acyl-, and trans-2-enoyl-) yield an incremental binding energy of about 800 cal/-CH2 group until a chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(84 citation statements)
references
References 46 publications
4
79
1
Order By: Relevance
“…Therefore, as demonstrated in the literature, VLCAD not only allows longer chain-length substrates to bind, but it prefers them (4). It has been shown for MCAD that substrate/ product binding energy increases linearly with chain length (390 cal/CH 2 group) (42). For ACADs, product release is the rate-limiting step (43).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, as demonstrated in the literature, VLCAD not only allows longer chain-length substrates to bind, but it prefers them (4). It has been shown for MCAD that substrate/ product binding energy increases linearly with chain length (390 cal/CH 2 group) (42). For ACADs, product release is the rate-limiting step (43).…”
Section: Resultsmentioning
confidence: 99%
“…It is a wellestablished fact that reduced MCADH with bound product (or product analogs) is reoxidized by molecular oxygen much slower than the reduced enzyme without the bound ligand (Beinert, 1963;Wang & Thorpe, 1991;Trieval et al, 1995). In their studies with redox-inactive analogs, Thorpe and coworkers (Trievel et al, 1995) have shown that the ligands which lack the carbonyl oxygen (e.g., thioether) are much less effective (at least 2 orders of magnitude) in protecting the reduced enzyme flavin toward molecular oxygen. This could be explained as following: First, the thioether ligand would bind less tightly to the enzyme than the corresponding thioester, due to lack of the two hydrogen bonds between the carbonyl oxygen to the flavin ribityl 2′-OH and to the main chain amide nitrogen of amino acid 376.…”
Section: Discussionmentioning
confidence: 99%
“…The 3-thia sulfur of 3S-C 8 -CoA lowers the pK a of the adjacent R-proton by approximately 5 pK units compared to n-octanoyl-CoA (16), for which a pK a ≈21 has been estimated (8,9). Hence, a pK a ≈16 for the RC-H of free 3S-C 8 CoA appears to be an educated guess.…”
Section: Formation Of Anionic Ligands Upon Binding To Mcadhmentioning
confidence: 99%